H.P. Lovecraft's The colour out of space - Tanabe, Gou, 1975- (Dark Horse Manga, a division of Dark Horse Comics LLC., 2025)
"Gou Tanabe's manga adaptation of H.P. Lovecraft's The Colour Out of Space, drawn in traditional Japanese comics style. In 1927, a surveyor in the backwoods hills beyond Arkham talks with a man he was warned not to believe-old Ammi Pierce. Ammi alone now remembers the full story behind the horrible events of decades ago...when a strange meteorite fell from space and warped and twisted the land with its unearthly radiance..."--